Implementing value-based healthcare: a scoping review of key elements, outcomes, and challenges for sustainable healthcare systems - Hanan Khalil; Mary Ameen; Charles Davies; Chaojie Liu (Frontiers in Public Health)
IntroductionValue-Based Health Care (VBHC) is an increasingly important healthcare paradigm that focuses on maximizing health outcomes relative to the cost of care delivered. Various healthcare organizations have adopted VBHC principles, but significant barriers remain in adapting care models, engaging stakeholders, and measuring outcomes. Moreover, the lack of standardized methods for measuring outcomes and financial sustainability further complicates the transition to VBHC. Understanding the factors that facilitate or hinder VBHC adoption is crucial to informing policy and practice for broader implementation. The objective is to map the literature addressing VBHC concerning population, study characteristics, funding models, outcome measures, and barriers and facilitators.MethodsFollowing the JBI methodology and the PRISMA-ScR reporting guidance, a scoping review was undertaken to include primary and secondary research on VBHC across various healthcare settings. Searches were undertaken in nine relevant databases. Peer-reviewed quantitative and qualitative studies published in English were included and analyzed. A total of 145 studies were included after screening 2,725 studies.ResultsThe findings show that the United States leads VBHC research, contributing 65% of the studies, followed by European countries. Cohort and cross-sectional studies were predominant, focusing on various populations, including hospitals, surgical patients, and cancer patients. Key findings highlight that Value-Based Purchasing and Time-Driven Activity-Based Costing models were the most frequently reported funding models. Traditional in-hospital care remains the dominant delivery model, with increasing interest in telemedicine. Outcome measure were diverse, ranging from patient-reported outcomes to cost savings for both patients and providers. Barriers to VBHC implementation include insufficient funding, fee-for-service model persistence, and resistance from healthcare professionals. Facilitators included strong leadership, multidisciplinary collaboration, and the use of digital tools.ConclusionThe review highlights the need for consistent outcome measurements, financial incentives, and improved data transparency to ensure the successful and scalable implementation of VBHC across healthcare systems. While VBHC shows promise in improving healthcare efficiency and quality, challenges remain in aligning financial and operational structures to fully support this paradigm shift.